Correlação anatomopatológica entre a amostragem por agulha ea amostragem cirúrgica no câncer de próstata: variabilidade interobservador - Sergio Geraldo Veloso (2007)
Prostatic adenocarcinoma has variable clinical evolution and the Gleason grading is its main prognostic factor. Diagnosis and classification are done through anatomic pathological testing which, although used to diagnose the neoplasia, can also show other present histological lesions. As a test, it needs reliability which is evaluated bythe interobserver agreement. In the study, three pathologists reviewed the biopsy slides and prostatic surgical specimens of 110 patients previously diagnosed as suffering from prostate cancer and who were referred to radical prostatectomy. All three observers filled in a histological protocol which dealt with prostatic neoplastic lesions and benign ones. Data were analyzed as for the interobserver agreementand as for the agreement between both specimens by the same observer, by the Kappa statistic. The reproducibility of the method was variable. In the biopsy, good agreement was found in the diagnosis of cancer (K=0,75). Moderate agreement was found in the most aggressive Gleason grade (K=0,45), in the tumor tissue proportion (K=0,44), in the presence of perineural invasion in the tumors (K=0,42), in inflammatory infiltration (K=0,44) and in a significant biopsy (K=0,43). The primaryGleason grade showed bad reproducibility (K=0,37). The worst agreement was in the diagnosis of PIN of high grade (K=0,11) and in the secondary Gleason grade (K=0,20). In the surgical tissue, the best reproducibility was in the cancer diagnosis (K=0,59), followed by the primary grade (K=0,47) and the most aggressive Gleason grade (K=0,45), the presence of perineural invasion (K=0,52) and NIP of high grade (K=0,36). The secondary Gleason grade had a bad agreement (K= 0,25) and the agreement was even worse in the diagnosis of inflammatory infiltration (K=0,08) and in the presence of benign prostatic hyperplasia (K=-0,05). In the surgical specimen, the Gleason score (K=0,46) obtained a better agreement than the modified Gleasonscore (K=0,36). In the needle biopsy, both scores were similar (K=0,36 and K=0,35, respectively). Comparing the three areas of the needle biopsies (apex, mid-prostate and base) with the respective areas of the surgical tissue, there is a good agreement between the primary and the most aggressive Gleason grade. It is clear that the isolated morphological analysis of specific criteria is based on low reproducibilitycriteria. Subjective components used in an anatomic pathological evaluation are not efficiently assessed by statistic methods. Improvement, not only in the methodology but also in the anatomic pathological criteria adopted worldwide, urges to be carriedout systematically.